PREDICTION ROLE OF THE LEFT VENTRICLE REMODELLING IN ARTERIAL HYPERTENSION PATIENTS - S. V. Ivanova; Yu. A. Vasyuk; E. L. Shkolnik; A. V. Khadzegova; I. A. Sinitsina (Российский кардиологический журнал, 2016)
Aim. To study the influence of various geometric models of the left ventricle (LV) on long-term prognosis in arterial hypertension (AH).Material and methods. Totally, 180 AH patients studied at the age 50,5±6,7 y.o., for 10 years of follow-up. All patients at the inclusion stage underwent standard clinical and functional investigation, 2D-echocardiography, 6-minute walking test, NT-proBNP.Results. By EchoCG theLV hypertrophy (LVH) was found 1,8 times more frequently than by ECG. Normal geometry of theLV was found in 25,5%, concentric LVH — 42,8%, eccentric LVH — 11,7%.Conclusion. By the multifactorial analysis, LVH was independent predictor of adverse prognosis and, in combination with other independent factors (age, male gender, 6-minute walking test, NT-proBNP level in plasma) did double the probability of an adverse cardiovascular risk.